THE RELATIONSHIP BETWEEN SELECTED KINETIC VARIABLES DURING THE PROPULSION AND FLIGHT PHASES IN THE 50M BUTTERFLY STROKE AMONG IRAQ’S NATIONAL YOUTH SWIMMING TEAM - Zaid Ali Obaied Essa; Ahmed Sami hassan; Maad abed Ibrahim; Dr .Maad Manea Allawe (Proximus Journal Publishing, 2025)
The study aimed to investigate the relationship between certain kinetic variables during the push-off and flight phases in the 50-meter butterfly swimming event among the Iraqi national youth team. The researchers hypothesized a statistically significant relationship between specific kinetic variables in the push-off and flight phases. A descriptive approach using the correlational method was adopted, as it was deemed the most appropriate and fluid for addressing the research problem
Keywords: Kinetics; Butterfly Swimming